The RNA binding protein CARHSP1 facilitates tumor growth, metastasis and immune escape by enhancing IL-17RA mRNA stabilization in prostate cancer - YiFan Jiang; Yanan Wang; KaiHua Xue; JianBin Ma; Shan Xu; Ke Wang; Peng Guo (Cell & Bioscience)
Abstract Background Calcium-regulated heat-stable protein 1 (CARHSP1) has been identified as a cold shock domain (CSD) protein family member, participating in the regulation of ribosomal translation, mRNA degradation, and the rate of transcription termination. However, there is an extremely limited understanding of the function of CARHSP1 as an RNA binding protein (RBP) in prostate cancer (PCa). Methods The expression pattern of CARHSP1 and the correlation between the CARHSP1 expression and clinical prognosis in PCa patients were analyzed by using multiple public databases. In vitro and in vivo functional assays were conducted to assess the role of CARHSP1. The mechanisms of CARHSP1 function on IL-17RA were identified by RNA pull-down and RNA stability assays. A co-culture model of Jurkat cells and PCa cells was established to investigate the potential role of CARHSP1 in tumor immunity of PCa. Results CARHSP1 was highly expressed in PCa, and correlated with advanced characteristics of PCa and unfavorable prognosis in PCa patients. Moreover, knockdown of CARHSP1 significantly dampened the capacity of proliferation, migration, invasion, and immune evasion of PCa cells in vitro and in vivo. Mechanistically, the RNA-binding protein CARHSP1 selectively bound to the mRNA of IL-17RA, resulting in the increased expression of both IL-17RA mRNA and protein. Downregulating expression of CARHSP1 shortened the half-life of IL-17RA mRNA and reduced its expression. Subsequently, the downstream pathways of IL-17RA, JAK-STAT3 signaling pathway and NF-κB signaling pathway, were activated by CARHSP1 and contributed to the malignant phenotype of PCa cells. Conclusions In conclusion, our results demonstrated that the increased expression of CARHSP1 in PCa is correlated with advanced clinical characteristics and unfavorable prognosis, and CARHSP1 may promote the progression of PCa through enhancing the mRNA stability of IL-17RA and activating its downstream pathways. These results suggest that CARHSP1 is an important regulator of tumor microenvironment in PCa, and CARHSP1-IL-17RA axis could be potential novel therapeutic targets for PCa.